Clashing Legal Realities: A Comparative Analysis of Insolvency Tests in Australia and Indonesia's Bankruptcy Law - Riyanto, R Benny; Arifin, Ridwan; Fibrianti, Nurul; Laryea, Emmanual; Syahputra, Bearlly Deo (Universitas Negeri Gorontalo, 2025)
This comparative study explores the insolvency test frameworks in Australia and Indonesia, focusing on the legal perspectives within their respective bankruptcy laws. In Australia, the insolvency test is governed by the Corporations Act 2001, which employs a dual approach: the balance sheet test, assessing whether liabilities exceed assets, and the cash flow test, evaluating a company's ability to meet debts as they fall due. This combination aims to offer a comprehensive picture of a company's financial health, facilitating early intervention to prevent insolvency. In contrast, Indonesia's insolvency regime, regulated by the Insolvency and Suspension of Debt Payment Obligations Law (UUPK), adopts a more creditor-centric approach, emphasizing the debtor's ability to meet debt obligations rather than focusing on asset-liability balances or cash flow. This disparity reflects differing legal frameworks and economic contexts, which in turn affect the efficiency and effectiveness of insolvency proceedings in each country. The study utilizes a comparative legal research approach, analyzing primary legal texts, case law, and secondary literature to examine the procedural differences, particularly in the initiation of bankruptcy claims and the protection of creditors' rights. It also explores how these divergent insolvency tests shape the resolution of financial distress, considering both legal and practical implications in the respective jurisdictions. The findings highlight key contrasts in how insolvency is defined and addressed, with Australia prioritizing preventative measures and a holistic view of financial health, while Indonesia's system places more emphasis on creditor protection and debt repayment capacity. The study concludes with recommendations aimed at improving alignment and efficacy within each legal framework, proposing adjustments that could enhance financial stability and optimize outcomes for stakeholders in both countries.